Etnobotani Tanaman Obat Demam dan Batuk di Provinsi Jawa Timur - Rima Suwistika; Mushoffa Mushoffa (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Fever and cough are diseases that often attack humans. Fever and cough are early signs of infection of a disease that attacks the body. This qualitative study was initiated to identify the types of plants, organs used, and local wisdom inherent in the traditional medicine practices of the people of East Java Province in dealing with fever and cough. Data collection was carried out through literature survey methods and journal reviews. Data sourced from articles in the Google Scholar, Google, and ResearchGate databases were then analyzed using a qualitative descriptive approach.The results of the study showed that there were 9 species of plants used for fever and cough medicine, including turmeric (Curcuma domestica), lime (Citrus X aurantiifolia), fennel (Foeniculum vulgare), starfruit (Averrhoa bilimbi L), kencur (Kaempferia galanga), mengkudu (Morinda citrifolia), katuk (Sauropus androgynus (L.) Merr), tapakliman (Elephantopus scaber), lemongrass (Adropogon nardus). The plant has certain content that can cure fever and cough. Fruit, leaves, rhizomes, and roots are parts of the plant organs that are often used by the community.